Detection of Carbohydrate Antigen 50 Based on a Novel Miniaturized Chemiluminescence Analyzer Enables Large-Scale Cancer Early Screening in Grassroots Community - Liu, Yu; He, Xiaowei; Zou, Jingjing; Ouyang, Xiuyun; Huang, Chunrong; Yang, Xiao; Wang, Yu (Frontiers in Bioengineering and Biotechnology, 2022)
Early screening of cancer can effectively prolong survival time and reduce cancer mortality. However, the existing health-monitoring devices can only be carried out in professional laboratories, so large-scale early cancer screening in resource-limited settings is hardly achieved. To embrace the challenge, we developed a novel chemiluminescence immunoassay (CLIA) analyzer that does not require a professional operation; then it was applied to detect carbohydrate antigen 50 (CA50), a non-organ-specific tumor marker for various cancers screening. As a result, the analyzer exhibited excellent performance that the total assay time was only 15 min, and the detection limit reached 0.057 U mL-1. A coefficient of variance (CV) less than 15% was well controlled for both intra-assay and inter-assay precision, and the linear range was 0-500 U mL-1. More importantly, this analyzer can continuously detect 60 samples per hour without any professional paramedic. Finally, this method has been applied to evaluate clinical samples and showed a good correlation with the clinical test results (correlation coefficient, 0.9958). These characteristics exactly meet large-scale and high throughput early screening of cancer. Thus, this miniaturized analyzer for CA50 detection is promising to achieve early large-scale screening of cancer in the resource-limited grassroots community.